SCIENTIFIC WRITING AS AN ART: AN OVERVIEW - A., Sreeja P.; S., Arya U.; Kumar, Akshara S.; S., Swathy (International Journal of Current Pharmaceutical Research, 2016)
Writing well is an art that takes time to be perfect, but if you don't try it, you won't nail it. The value of writing should never be underestimated, as writing well improves your work [1]. If the writing is clear, it can turn bad science into good science and makes more impactful and valuable [1]. Writing helps the speaker to express the issue before audience very easier. There are various types of writing such as articles, journals, literature review etc [3]. The scientific writing should be simple, objective and concise. Writing depends on the reader's needs (for a normal reader technical terms mathematical expressions has never suited well) [2]. Various types of manuscripts are used in scientific writing. One of the key developers in scientific publications is the adoption of the IMRAD's [Introduction, Methods, Results and Discussion] structure [5]. Apart from this other form is TAKAR (Title, Abstract, Keywords, Acknowledgements, and References) [5]. Approaches made by writers for in the design of the contents are about various forms in more than one journal [4]. In case of reference also various styles are used, such as Vancouver's style, the Harvard system. Writing is a most important factor to criticize and evaluate the publications [9]. Writing process should not intend to be sane, effective. Writing is a decision making process and Writers designs in different ways for their scientific work [7]. All written communications are affected by a larger context or situation [8]. This article helps the reviewers to know about the different writing methods its rhythm and styles.